Enhanced ice sheet melting driven by volcanic eruptions during the last deglaciation - Francesco Muschitiello (Nature Portfolio, 2017)
The impact of volcanism on ice sheet melting during the last deglaciation is poorly understood and limited by a lack of suitable proxies. Here, the authors combine annually resolved records of ice sheet melting with numerical models to show that ice sheets are sensitive to high-latitude volcanic eruptions.